Directed Graphene‐Based Nanoplatforms for Hyperthermia: Overcoming Multiple Drug Resistance. (3rd August 2018) - Tu, Zhaoxu; Qiao, Haishi; Yan, Yuting; Guday, Guy; Chen, Wei; Adeli, Mohsen; Haag, Rainer
Abstract: Multidrug resistance (MDR), which leads tumors resistance to traditional anticancer drugs, can cause the failure of chemotherapy treatments. Herein, we present a new way to overcome this problem using smart multifunctional graphene‐based drug delivery systems which can target subcellular organelles and show synergistic hyperthermia and chemotherapy. Mitochondria‐targeting ligands are conjugated onto the doxorubicin‐loaded, polyglycerol‐covered nanographene sheets to actively accumulate them inside the mitochondria after charge‐mediated cellular internalization. Upon near‐infrared (NIR) irradiation, adenosine triphosphate (ATP) synthesis and mitochondrial function were inhibited and doxorubicin released into the cellular interior. The hyperthermia‐accelerated drug release led to a highly selective anticancer efficiency, confirmed by in vitro and in vivo experiments.